Comparing pedigree and genomic inbreeding coefficients, and inbreeding depression of reproductive traits in Japanese Black cattle - Motohide Nishio; Keiichi Inoue; Shinichiro Ogawa; Kasumi Ichinoseki; Aisaku Arakawa; Yo Fukuzawa; Toshihiro Okamura; Eiji Kobayashi; Masaaki Taniguchi; Mika Oe; Kazuo Ishii (BMC Genomics, 2023)
Abstract Background Pedigree-based inbreeding coefficients have been generally included in statistical models for genetic evaluation of Japanese Black cattle. The use of genomic data is expected to provide precise assessment of inbreeding level and depression. Recently, many measures have been used for genome-based inbreeding coefficients; however, with no consensus on which is the most appropriate. Therefore, we compared the pedigree- ( $${F}_{PED}$$ F PED ) and multiple genome-based inbreeding coefficients, which were calculated from the genomic relationship matrix with observed allele frequencies ( $${F}_{GRM}$$ F GRM ), correlation between uniting gametes ( $${F}_{UNI}$$ F UNI ), the observed vs expected number of homozygous genotypes ( $${F}_{HOM}$$ F HOM ), runs of homozygosity (ROH) segments ( $${F}_{ROH}$$ F ROH ) and heterozygosity by descent segments ( $${F}_{HBD}$$ F HBD ). We quantified inbreeding depression from estimating regression coefficients of inbreeding coefficients on three reproductive traits: age at first calving (AFC), calving difficulty (CD) and gestation length (GL) in Japanese Black cattle. Results The highest correlations with $${F}_{PED}$$ F PED were for $${F}_{ROH}$$ F ROH (0.86) and $${F}_{HBD}$$ F HBD (0.85) whereas $${F}_{GRM}$$ F GRM and $${F}_{UNI}$$ F UNI provided weak correlations with $${F}_{PED}$$ F PED , with range 0.33–0.55. Except for $${F}_{GRM}$$ F GRM and $${F}_{UNI}$$ F UNI , there were strong correlations among genome-based inbreeding coefficients ( $$\ge$$ ≥ 0.94). The estimates of regression coefficients of inbreeding depression for $${F}_{PED}$$ F PED was 2.1 for AFC, 0.63 for CD and -1.21 for GL, respectively, but $${F}_{PED}$$ F PED had no significant effects on all traits. Genome-based inbreeding coefficients provided larger effects on all reproductive traits than $${F}_{PED}$$ F PED . In particular, for CD, all estimated regression coefficients for genome-based inbreeding coefficients were significant, and for GL, that for $${F}_{UNI}$$ F UNI had a significant.. Although there were no significant effects when using overall genome-level inbreeding coefficients for AFC and GL, $${F}_{ROH}$$ F ROH provided significant effects at chromosomal level in four chromosomes for AFC, three chromosomes for CD, and two chromosomes for GL. In addition, similar results were obtained for $${F}_{HBD}$$ F HBD . Conclusions Genome-based inbreeding coefficients can capture more phenotypic variation than $${F}_{PED}$$ F PED . In particular, $${F}_{ROH}$$ F ROH and $${F}_{HBD}$$ F HBD can be considered good estimators for quantifying inbreeding level and identifying inbreeding depression at the chromosome level. These findings might improve the quantification of inbreeding and breeding programs using genome-based inbreeding coefficients.